Information sharing in governance of flood management in Malaysia: COBIT based framework - Maidin, Siti Sarah; Othman, Marini; Ahmad, Mohammad Nazir (IEEE, 2014)
Due to the frequent occurrences of catastrophic disasters worldwide, several measures and approaches have been implemented by governments in an attempt to overcome and alleviate the hazards and risks. To date, governance has been identified as a crucial element by which to drive effective Flood Management (FM). The aim of this paper is to identify the challenges related to information sharing in the current structure and propose a governance framework to oversee FM. A qualitative field study is employed to identify challenges in managing information within FM. The paper concludes by making recommendations for the improvement of FM practices in Malaysia with emphasis on governance by utilizing the Control Objectives for Information and Related Technology (COBIT) framework.